Singular times and multiple temporalities of the future in tourism planning - Ricaurte-Quijano, Carla (2024)
Critical thinking about the future needs to be at the centre of tourism planning scholarship. By using complexity theory as a framework to understand the shaping power of time, we review understandings about the future in tourism planning literature concerning three interrelated aspects: How the future is known in tourism planning, how the future has been planned in tourism, and what futures have been planned. Changing, diverse and mutually intertwined views of understanding time and approaching the future are identified and gathered into two interwoven bundles. In the first bundle, the future in tourism planning is singular, foreseeable, and technical, with strong linear and cause-effect assumptions. In the second grouping, as cause-effect assumptions are questioned, futures in tourism planning become multiple, nested, simultaneous and emerge from non-linear, relational, value-laden and time-dependent socio-political processes. A characterisation of singular time and multiple temporalities in tourism planning is presented, and their coexistence in the literature is acknowledged for its potential to stimulate ethical future-making through planning and tourism.